PEMBANGUNAN APLIKASI SERVER RUN TRACKER - Parasian D. Silitonga; Tiffani Aycristin Br Sembiring (PUBLIKASI ILMIAH TEKNOLOGI INFORMASI NEUMANN (PITIN), 2017)
Development of the Run Tracker application is designed with a server application, where runner data, event data and trophy data and data feeds that use the Run Tracker application can be collected in a computerized database. The process of delivering this information can be done using an internet connection. The development of this server application aims to communicate with the Run Tracker application on mobile devices